Replacing Detonation by Compressed Balloon Approaches in Finite Element Models. (12th May 2020) - Legrand, Pierre; Kerampran, S.; Arrigoni, M.
Abstract : The evaluation of blast effects from malicious or accidental detonation of an explosive device is really challenging especially on large buildings. Indeed, the time and space scales of the explosion together with the chemical reactions and fluid mechanics make the numerical model really difficult to achieve acceptable structural design. Nevertheless, finite element methods and especially Arbitrary Lagrangian Eulerian (ALE) have been extensively used in the past few decades with some simplifications. Among them, the replacement of the explosive event by a compressed balloon of detonation products has been proven useful in numerous different situations. Unfortunately, the ALE algorithm does not achieve a proper energy balance through the numerical integration of the discrete scheme; this important drawback is not compensated by the use of the classical compressed balloon approach. The paper focuses on increasing the radius of the equivalent ideal gas balloon in order to achieve better energy balance and thus better results at later stages of the blast wave propagation.